Regional GDP – Investment Nexus: Empirical Analysis through Classical Production Function - Raycheva, Iva; Boshnakov, Venelin (Research Papers, 2018)
The paper presents selected results from empirical analysis of the interrelation between the regional levels of investment and GDP. Classical models of production functions are estimated after their double-log transformation into linear regression equations. Annual data for the years 2000-2015 measured at NUTS-3 regional level is utilized in respect of the district employment, GDP, and the regional investment measured by the expenditures on fixed assets acquisition.